PL03.1 STIs - 2013: Resurgence of Early Syphilis, Persistence of High STI Morbidity and Mortality, and Emergence of Antimicrobial Resistant STIs: Implications and Potential Responses. (13th July 2013) - Holmes, K
Abstract : Recent directions in clinical-epidemiologic research on STIs include (1) population-level estimates of STI prevalence (e.g., WHO's 2011 publication of global estimates), and formal population-level surveys of STI prevalence and risk determinants; (2) analysis of global mortality and disability attributable to major diseases, including STIs (the Global Burden of Disease Study, published in the December 2012 triple issue of The Lancet); (3) conceptualization and implications of the "Treatment and Care Cascade" and the "Prevention Cascade" currently focused on HIV infection; and (4) emerging interest in Program Science, linking programme implementers and scientists in needs assessments, conceptualization, design, advocacy for funding, implementation, evaluation, cost-effectiveness, and continuous strengthening of STI/HIV programmes. The global emergence and rapid spread of anti-microbial resistant pathogens, suggests the clinical mantra of "first do no harm" to the individual patient must be mirrored in a similar public health mantra - "first do no harm" to the population. This means selective use and more systematic evaluation of the impact of antimicrobial use on human and animal pathogens and microbiomes. The reemergence of syphilis and persistence of other STIs in vulnerable populations, and the limited implementation of cost-effective interventions for STI control reflects global neglect of STI programmes, and perhaps increasing failure to effectively integrate STI, HIV/AIDS, and reproductive health programmes globally (for example, the very limited integration of HIV PMTCT with elimination of congenital syphilis programmes). Nonetheless, progress in sexual health promotion and STI control can be made possible with cost-effective use by clinicians and public health leaders of effective, available tools, such as scale up of HPV and HBV vaccines, and linked delivery of other sociobehavioral and biomedical STI interventions in vulnerable populations. Rigorous evaluation of the impact of such programmes, with assessment of what is not working as well as what is working, is essential.